Inverse nodal problem with eigenparameter boundary conditions - Ic, Unal; Koyunbakan, Hikmet (Springer Heidelberg, 2024)
The reconstruction of potential function using nodal parameters is an inverse problem that has been studied in this work. An efficient and highly helpful transformation allowed for the extraction of a reconstruction formula for the problem's potential function by a narrow collection of nodal data only. Additionally, the method's efficacy was shown by a few numerical illustrations.
Keywords: Nodal parameters; Sturm-Liouville equation; Pr & uuml;fer substitution